Assessment: The Quality of Instrument to Measure Student’s Scientific Attitude (SSA) based on Content Validity and Empirical Testing - Alexander Andi Kurnianto; Mundilarto Mundilarto (Postgraduate, University of Mataram, 2023)
This research aims to determine the questionnaire quality based on: (1) content validity, and (2) empirical testing. The research was research and development using the 4-D model (defining, designing, developing, and disseminating stage). The instrument validation was conducted by an instrument expert, two physics teachers, and five peer reviewers. The subject of empirical testing was 206 students of class XII IPA SMAN 6 Yogyakarta in the 2019/2020 school year. The research instrument was a questionnaire of student’s scientific attitude (SSA) that consists of 20 statement items. The data were analyzed using the raw scale for content validity of the SSA questionnaire, and Product Moment Pearson for empirical testing validation using SPSS 16, and Cronbach’s Alpha value to determine the reliability. The results show that (1) all items of the SSA questionnaire meet content validity with raw scale score between 3.75 and 4, which means on excellent category; (2) the SSA questionnaire meet empirical validity with Product Moment Pearson r between 0.186 and 0.595; all r > rtable: 0.138 (n=206; α = 0.05), and meet reliability with Cronbach’s Alpha value between 0.724 and 0.756; all value > 0.60; which means the SSA questionnaire are feasible to use based on empirical testing